Методика расчета надежности всыпных обмоток асинхронных электродвигателей мощностью от 0,18 до 100 КРТ: № ОТЭ.139.174 - Постов И.; Штуцен Л.; Стрельбицкий Э. К. Эдуард Карлович; Федоров В.; Муравлев О. П. Олег Павлович; Похолков Ю. П. Юрий Петрович (Томск, Изд-во ТПИ, 1967)
Ротапринт. изд.